Current Developments in Monetary and Financial Law, Vol. 4. (International Monetary Fund, 2008)
The Legal Department and the Institute of the IMF held their ninth biennial seminar for legal advisors of IMF member countries' central banks, and the papers published in this volume are based on presentations made by officials attending this seminar. The seminar covered a broad range of topics, including sovereign debt restructuring, money laundering and the financing of terrorism, financial system and banking supervision, conflicts of interest and market discipline in the financial sector, insolvency, and other issues related to central banking.